Peran Guru Kelas Mengatasi Bullying Verbal Di Sekolah Dasar Inpres Ndona III Kabupaten Ende - Berty Sadipun; Aschari Senjahari Rawe; Geryani Suryo Moan Kala (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
The purpose of the research based on the problem formulation above is: "To find out the role of class teachers in overcoming verbal bullying at SDI Ndona. The problem of this research is what are the roles of class teachers in overcoming verbal bullying at SDI III Ndona. This research method is qualitative, with data collection used namely interviews, observation and documentation. Data analysis used is data collection, data reduction, data presentation and drawing conclusions. The results of the study show that class teachers play a role in overcoming verbal bullying in various ways according to the role of teachers in schools, namely: 1) As teachers, teachers play a role by integrating anti-bullying values ​​​​in learning. 2) As educators, teachers play a role through role models and character building. 3) As mentors, teachers play a role with a counseling and collaboration approach